INTERNET MEDIUM ALTERNATIF PUBLIC RELATIONS - Melita, Yerah (Istek Widuri Jakarta, 2015)
Various attempts were made by the Public Relations of an organization / company to convey information to the public, both internally and externally. Messages delivered Public Relations can be made directly or indirectly. Organization/ company can interact with the public through the activities carried out through the via medium of communication. One of Public Relations medium to deliver a message is the internet.Through the Internet, as one alternative medium used Public Relations organization/ company communication messages are expected to suit its purpose well.The purpose of the organization / company that is maintaining and the creation of a harmonious relationship between the organization / company with both internal and external publics can be realized, so that the public can support any activity undertaken the organization / company.